Development of Youtube-Assisted Learning Videos on Science Subject (Mupel) Content - Widodo, Temon Slamet; Sumilah, Sumilah (Universitas Negeri Semarang, 2020)
This study aims to develop youtube-assisted learning videos to improve science learning outcomes of fifth grade students of Kalibanteng Kidul Public Elementary School 03. This study uses a research development (RD) approach based on Sugiyono's theory which has been adjusted to research needs into eight stages of implementation. The results of this study indicate that: (1) learning videos developed according to the questionnaire of the needs of students and teachers; (2) valid learning videos based on validation from material experts and media experts. Obtained a percentage of 100% with a very feasible category of material experts and a percentage of 78,3% with a decent category from media experts; (3) the percentage of teacher responses after using a learning video in a classical manner is 98% with very good criteria, the percentage of students' responses in a classical manner is 98,5% with criteria agreed; (4) the use of learning videos has very good practicality, because in practicality tets get a percentage 90%; (5) learning videos are effectively used in science learning, the results of the analysis of the difference in the average t-test are 0,000 and the increase in average (gain) was 0.57 with high criteria. The conclusions of the results of this study are that learning videos were suitable for use in learning activities 000 and the increase in average (gain) was 0.57 with high criteria. The conclusions of the results of this study are that learning videos were suitable for use in learning activities 000 and the increase in average (gain) was 0.57 with high criteria. The conclusions of the results of this study are that learning videos were suitable for use in learning activities